Moderate multidimensional poverty index: paving the way out of poverty - Alkire, S; Kovesdi, F; Scheja, E; Vollmer, F (Oxford Poverty and Human Development Initiative, 2022)
Eradicating poverty in all its forms, everywhere, requires indicators that measure sustainable pathways out of poverty, and not only the absence of acute poverty. This paper introduces a trial Moderate Multi¬dimensional Poverty Index (MMPI) that reflects moderate rather than acute levels of multidimensional poverty. The MMPI adjusts nine of the 10 indicators of the global Multidimensional Poverty Index (global MPI) to reflect moderate poverty and create a meaningful superset of the acutely poor population. Although data-constrained, the trial MMPI outlines a methodology and potential indicators for a measure that would: i) be meaningful and comparable across populations at higher levels of development; ii) align with higher standards defined in Agenda 2030; and iii) provide insight into aspects of intrahousehold deprivation. The MMPI is illustrated empirically using nationally representative household surveys from Bangladesh, Guatemala, Iraq, Serbia, Tanzania and Thailand. The results confirm the added value of having three nested measures of destitution, acute, and moderate multidimensional poverty. The MMPI also complements monetary measures with informative differences in poverty levels observed. The results demonstrate that a Moderate MPI is a desirable global poverty index, which is likely to illuminate thus far hidden aspects in of multidimensional poverty, such as intrahousehold deprivations in education. Challenges remain regarding data availability, and further study across additional countries is required before the MMPI structure can be finalised.